CHANGE OF BEHAVIOR AND IMPROVEMENT OF COMMUNITY SKILLS IN PREVENTING AND CONTROLLING BLOOD LIPID LEVELS DURING THE COVID 19 PANDEMIC AREA OF PALEMBANG SOCIAL HEALTH CENTER - Susyani, Susyani; Terati, Terati; Telisa, Imelda (LPPM Univ. Ibn Khaldun Bogor, 2022)
Manifestations of lifestyle changes are physical activity, and changes in unhealthy eating patterns including a diet high in fat, carbohydrates, and low fiber intake one of the reasons for degenerative diseases, namely dyslipidemia. The cause of changes in blood lipid profiles is a diet that can be influenced by nutritional knowledge and a person's attitude. The older the age, the lower the body's metabolic function. For this reason, the target of this community service activity is the elderly. The purpose of this study was to determine the knowledge and skills of the community through education about healthy lifestyles in an effort to prevent dyslipidemia and control blood lipid levels in members and cadres of the Teratai Elderly Integrated Healthcare Center in the Work Area of the Palembang Social Health Center. The activity was carried out at the Integrated Healthcare Center which has elderly members under the guidance of the Palembang Social Health Center. Community service activities were carried out 2 times in Nutrition Education in the form of espionage and counseling for Integrated Healthcare Center members and 1 training for Posyandu cadres. From the results of measuring cholesterol levels, 10 people (32.25%) with cholesterol levels above normal. In addition, this community service activity is expected to increase the knowledge of nutrition and health for elderly Integrated Healthcare Center members and Teratai Integrated Healthcare Center cadres about balanced nutrition and how to make fruit and vegetable smoothies in preventing dyslipidemia.